Adolescent sexual aggressiveness and pornography use: A longitudinal assessment. Issue 6 (20th August 2019) - Dawson, Kate; Tafro, Azra; Štulhofer, Aleksandar
Abstract : Abstract: The rising prevalence of (online) pornography use among, mostly male, adolescents revived social concerns regarding possible effects of pornography use on sexual aggressiveness. Given the paucity of longitudinal explorations of this link, this study focused on the following two research questions: (Q1) Is pornography use during middle to late adolescence related to male adolescents' self‐reported sexual aggressiveness; and (Q2) can personality traits and characteristics that have been associated with sexual aggression account for this presumed link? Using data from a six‐wave panel sample of 594 male Croatian high‐school sophomore students ( M age at baseline  = 15.8 years, SD  = 0.52), latent class and latent growth curve modeling were employed to answer these questions. There was a significant baseline difference in the frequency of pornography use between participants who reported no or marginal levels of sexual aggressiveness during the period under observation (20 months) and their peers who reported substantial sexual aggressiveness, with the former reporting significantly lower initial levels of pornography use compared to the latter. Controlling for personality characteristics did not cancel this association. In addition, bullying and reported peer pressure significantly predicted initial levels of pornography use, but not its subsequent change. With the controls omitted from the analysis, a slight average increase in pornography use was observed among adolescents who reported no or lowest levels of sexual aggressiveness. In contrast, pornography use decreased somewhat among their peers who reported moderate sexual aggressiveness. Insights from this study can contribute to school‐based sexual violence prevention programs, as well as inform recently proposed pornography literacy programs which aim to assist adolescents in navigating the increasingly sexually explicit online environment.